2012
DOI: 10.1186/1744-859x-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Number of prior episodes and the presence of depressive symptoms are associated with longer length of stay for patients with acute manic episodes

Abstract: BackgroundFew studies have analyzed predictors of length of stay (LOS) in patients admitted due to acute bipolar manic episodes. The purpose of the present study was to estimate LOS and to determine the potential sociodemographic and clinical risk factors associated with a longer hospitalization. Such information could be useful to identify those patients at high risk for long LOS and to allocate them to special treatments, with the aim of optimizing their hospital management.MethodsThis was a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In contrast to previous studies, we found no association between mixed mood and either quality of life or functioning in the present study. Further, previous studies have suggested that mixed symptoms in patients with bipolar disorder are associated with poorer prognosis and aggravated long‐term course of illness, including poorer treatment response , increased risk of relapse , decreased quality of life , decreased functioning and increased risk of suicide . In addition, in exploratory analyses we found results suggesting that there is no association between subsyndromal clinically rated manic symptoms and functioning and quality of life respectively.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…In contrast to previous studies, we found no association between mixed mood and either quality of life or functioning in the present study. Further, previous studies have suggested that mixed symptoms in patients with bipolar disorder are associated with poorer prognosis and aggravated long‐term course of illness, including poorer treatment response , increased risk of relapse , decreased quality of life , decreased functioning and increased risk of suicide . In addition, in exploratory analyses we found results suggesting that there is no association between subsyndromal clinically rated manic symptoms and functioning and quality of life respectively.…”
Section: Discussionmentioning
confidence: 39%
“…However, a substantial proportion of patients with bipolar disorder experience subsyndromal symptoms on a daily basis, and this has been associated with impaired functioning, increased risk of hospitalization, high risk of relapse, and comorbid substance use disorder , overall emphasizing the chronic and serious nature of bipolar disorder. Within bipolar disorder, mixed states and mixed symptoms represent a complex and heterogenous syndrome which has been associated with overall poorer prognosis and aggravated long‐term course of illness, including poorer treatment response , increased risk of relapse , decreased quality of life , decreased functioning and increased risk of suicide .…”
Section: Introductionmentioning
confidence: 99%
“…The p21-activated kinases (PAKs) are well-characterized Rac and Cdc42 effector proteins, which are involved in a variety of signaling pathways [38]. PAK2 has been shown to phosphorylate and activate c-Abl [39].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to length of stay (LOS) in hospital for mood disorder patients, several correlates have been suggested, ranging from sociodemographic features (age, being a housewife, living alone), clinical features (correlation with life events as being in grief for a loss, number of previous episodes and admissions, melancholic features, negative symptoms, increased dependence for instrumental activities of daily living, comorbid alcohol or drug-related disorders) and treatment type [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%